Mercure de France (Chez Guillaume Cavelier, 1724)
Includes separately paged section: Journal politique de Bruxelles, June 1778-Nov. 1789; Mercure historique et politique de Bruxelles (varies slightly), Dec. 1789-Dec. 1791.